Pendidikan Agama Islam dan Strategi Melawan Radikalisasi Kekerasan di Spanyol - Ramayanti, Ani (ARZUSIN, 2022)
Spain’s public schools need Islamic religious education to prevent terrorism. This is because many children in Spain’s schools are Muslim, which means they need to be educated about Islamic religious ideas. This is why Spain passed a law for Islamic religious education in public schools. They also passed new legislation that emphasized adaght against Islamic terrorism. These laws gave teachers of Islamic Education a significant role in countering Islamic terrorist messages and preventing violent radicalization.